Action or word – what lies at the heart of the first philosophy? - Pokorski, Bartosz (Hybris, 2018)
In this paper I compare the philosophy of being, which has its model example in the philosophy of Aristotle, with the philosophy of action proposed by Stanisław Brzozowski. These two constructions differ in their consideration starting point. The first one chooses the word as a start, while the second chooses an act. I tried to show contrast between these two positions and the consequences in the philosophical practice that depend on their primary assumptions. I discuss the differences between the philosophy that deals with things of the objective realm, that now becomes metascience and the philosophy of culture, which deals with the subject and the historically made world of human experience that was created by the working generations of men. The importance of this difference is essential if we want to ask a philosophical question about the crisis of culture